Smart sensors for structural health monitoring (SHM) - Suhadi, Nor Aisyah; Abdul Rahim, Ruzairi; Yunus, Yusri; Leow, Pei Ling; Mohammad Din, Shahrulnizahani (Penerbit UTHM, 2017)
Structural health monitoring (SHM) is a technique to diagnose an accurate and reliable condition of civil infrastructure by collecting and analyzing responses from distributed sensors. In recent years, aging civil structures have been increasing and they require further developed SHM technology for development of sustainable society. Wireless smart sensor and network technology, which is one of the recently emerging SHM techniques, enables more effective and economic SHM system in comparison to the existing wired systems. Researchers continue on development of the capability and extension of wireless smart sensors, and implement performance validation in various in laboratory and outdoor full-scale experiments.[1] the uses of wireless smart sensors has been contributing to the progress of SHM these past years. But the uses of it are still being investigated by the researchers to utilize it to its possible fullest capability.